The Effectiveness of Implementing the Sorogan Method in Higher Education: A Case Study of the Department of Al-Qur'an and Tafsir Studies - Deni Setiawan; Fitriana Firdausi (al-Afkar, Journal For Islamic Studies, 2025)
This study explores the dynamics of implementing the sorogan method, a traditional learning approach in pesantren, within the Qur'anic Studies and Tafsir Department at UIN Sunan Kalijaga. The main objective of this implementation is to train and familiarize students with accessing Arabic-language canonical references. Analyzed qualitatively through a case study approach, data were collected through interviews with faculty and students, as well as non-participant direct observations during several lecture sessions. The findings reveal that while this method enhances the personal internalization of understanding, it also faces challenges such as time constraints and difficulty in formulating a format that integrates with the modern curriculum. This study also provides analyses that can serve as considerations and recommendations for optimizing the sorogan method in higher education learning.